Efecto de los silicatos aluminicos calcicos sodio hidratados (hscas) en el crecimiento y sobrevivencia litopenaeus vannamei en sistemas intensivos - De La Torre Mejia, Jose Riquelme (Machala : Universidad Técnica de Machala, 2022)
Aquaculture is setting a precedent around the historical maximums of production worldwide, being crustaceans the group of species with the highest demand as a source of animal protein. Among the crustaceans we have the peneids; Litopenaeus vannamei or Pacific white shrimp, the most produced in intensive and intensive systems at different salinity ranges. The white shrimp is a species resistant to changes in salinity and other factors, which is why it is the favorite when selecting it for cultivation at higher densities. However, due to the intensification of cultivation, there is a greater danger of disease proliferation, in addition to toxic compounds produced by fungi such as mycotoxins, making this a sanitary problem affecting not only the crop but also the environment and bringing economic consequences, since the animals tend to become immunosuppressed, reducing weight gain and at the same time lowering productivity per pool. There are natural and artificial products, called calcium sodium hydrated aluminosilicates, which are responsible for sequestering these mycotoxins preventing them from bringing negative effects on the crop, and also help to reduce other toxic compounds such as ammonium and ammonia to less toxic compounds, thus maintaining, with the application in the pool, the health of organisms, increasing productivity, natural food available and lower amounts of toxic compounds. The ionic balance balances the minerals and allows a relationship between them so that the shrimp can develop better in better conditions and can survive in the fattening pools. Potassium, sodium, calcium and magnesium in optimal salinities are the most important ions that stand out for growth and development for shrimp, because Magnesium is the essential ion as a component of the exoskeleton of crustaceans. Potassium contributes to cells, is found in all fluids and soft tissues of the body and acts in the regulation of intracellular osmotic pressure. Calcium contributes to the growth of shrimp and formation of the exoskeleton after molting, hardening the shell of the shrimp. Potassium is essential, but it depends on the species, the density that is planted, the salinity that is found, the amount that will be needed will depend on the factors. Low concentrations of potassium and magnesium can affect shrimp survival and growth in low salinity waters. Shrimp farming requires food, which must provide what is necessary in relation to nutrients so that it can have normal growth and without inconveniences, however, there is a problem and that is that the cost of food often exceeds 50%. of total costs, making a good study and selection necessary, verifying which diet provides us with optimal nutrients to obtain the expected results. Among the essential nutrients we have proteins which provide energy to the shrimp so that it can perform its functions normally knowing that the animal's body is made up of 70% protein, in turn, the amounts vary depending on the stage in which be found.
El balance iónico equilibra los minerales y permite una relación entre ellos para que se los camarones se puedan desarrollar de una mejor manera en mejores condiciones y puedan sobrevivir en las piscinas de engorde. El potasio, sodio, calcio y magnesio en salinidades optimas son los iones más importantes que se destacan para el crecimiento y desarrollo para el camarón, debido a que el Magnesio es el ion esencial como componente del exoesqueleto de los crustáceos. El Potasio aporta para las células, se encuentra en todos los fluidos y tejidos blandos del organismo y actúa en la regulación de la presión osmótica intracelular. El Calcio aporta para el crecimiento de los camarones y formación del exoesqueleto después de la muda, endurando el caparazón del camarón. El Potasio es indispensable, pero depende de la especie, densidad que se siembre, la salinidad que se encuentre, la cantidad que se necesitará dependerá de los factores. Las bajas concentraciones de potasio y magnesio pueden afectar la supervivencia y el crecimiento del camarón en aguas de baja salinidad. El cultivo de camarón requiere de alimento, el cual, debe aportar lo necesario en relación a nutrientes para que pueda tener un crecimiento normal y sin inconvenientes, sin embargo, existe un problema y es que el costo del alimento supera en muchas ocasiones el 50% de costos totales haciendo necesaria un buen estudio y selección verificando que dieta nos provee de nutrientes óptimos para obtener los resultados esperados. De entre los nutrientes esenciales tenemos a las proteínas las cuales aportan de energía al camarón para que pueda realizar sus funciones con normalidad sabiendo que el cuerpo del animal está constituido del 70% de proteínas, a su vez, las cantidades varían dependiendo el estadío en que se encuentre.
Keywords: NITRÓGENO AMONIACAL TOTAL (TAN); AMONIACO (NH3); AMONIACO (NH3); SISTEMAS INTENSIVOS